Evaluating Protic Ionic Liquid for Woody Biomass One-Pot Pretreatment plus Saccharification, Followed by Rhodosporidium toruloides Cultivation - Rigual, Victoria; Papa, Gabriella; Rodriguez, Alberto; Wehrs, Maren; Kim, Kwang Ho; Oliet, Mercedes; Alonso, M. Virginia; Gladden, John M.; Mukhopadhyay, Aindrila; Simmons, Blake A.; Singh, Seema (American Chemical Society, 2020)
Woody biomass feedstocks pose challenges in their use as sustainable carbon sources due to their recalcitrance. One-pot ionic liquid-based processes are a promising bioproduction strategy to reduce water consumption (removing the washing of biomass), reduce costs, and minimize the presence of inhibitory compounds. We evaluated the one-pot ionic liquid pretreatment + saccharification configuration as a scheme for the deconstruction and conversion of two different woody feedstocks, eucalyptus, and pine. A comparative study of protic ionic liquids 2-hydroxylethylammonium acetate-based ionic liquids, bis-2-hydroxyethylammonium acetate, and cholinium lysinate for pretreatment of eucalyptus and pine was conducted. The impact of ionic liquids at 11% w/w on the saccharification and toxicity of hydrolysates containing the ionic liquid for downstream use for microbial cultivation was evaluated. Protic ionic liquids were more effective in eucalyptus than in pine pretreatment and less toxic than cholinium lysinate at concentrations <= 10% w/w. 2-hydroxylethylammonium acetate yielded the highest digestibility, of up to 75% in eucalyptus. As a proof of concept of an integrated feedstocks-to-biofuels process, we tested the growth of the fungal strain Rhodosporidium toruloides in hydrolysates with low amounts of ionic liquids and phenolic compounds. The proof of concept demonstrated the ability of Rhodosporidium toruloides to grow in the presence of 2-hydroxyethylammonium acetate (5% w/w), the importance to adjust the pH after saccharification, and the ability to consume lignin monomers. This work offers a valid starting point for further studies aimed at increasing cellulose digestibility in a one-pot configuration in the presence of protic ionic liquids.
Keywords: ENZYMATIC-HYDROLYSIS; RICE STRAW; LIGNOCELLULOSIC BIOMASS; LIGNIN CONTENT; CELLULOSE; CHOLINIUM; DEPOLYMERIZATION; RECALCITRANCE; DEGRADATION; EUCALYPTUS